Determinants of the cost of equity of Malaysian firms - Foong, S.S.; Goh, K.L. (2010)
A number of Capital Asset Pricing Model (CAPM) and its variants are considered in this paper for exploring the determinants of the cost of equity of Malaysian firms. The semi-deviation approach is shown to yield the highest explanatory power on the returns of firms. The estimates of cost of equity from the semi-deviation approach were regressed on a list of potential determinants in a panel model analysis. The results show that firm size, book-to-market ratio, payout ratio and return to equity are negatively related to the cost of equity.